The 2017–18 design and construction of ice composite structures in Harbin. (April 2019) - Pronk, Arno; Mistur, Mark; Li, Qingpeng; Liu, Xiuming; Blok, Rijk; Liu, Rui; Wu, Yue; Luo, Peng; Dong, Yu
Abstract: This paper will focus on the design and construction of two large thin shell structures with ice composites in the winter of 2017–18: the Flamenco Ice Tower and THRICE. Both structures were unique with regard to the application of ice composites. In this paper there will be a special focus on the structural behavior of the fiber-reinforced ice shell and membrane moulding. The ice composite had limited structural capacity and the material was pushed to its limits. Ice can be reinforced by adding (cellulose) fibers such as wood and paper. These fibers make the ice up to three times stronger and increase the ductility, thus creating a reliable building material. This sustainable, fully recyclable building material might be a solution for temporary constructions in cold areas, ice events, the Olympic Winter Games or possibly even Mars missions. HIT in cooperation with IASS Workgroup 21 invited several universities to design and construct architectural ice structures. In this paper the two most interesting structures that have been realized will be described. The technique used might also be interesting for architectural shell structures in other materials such as concrete and polymer composites. The Flamenco Ice Tower was the world record for the largest thin shell structure in ice and achieved the WA design award for most innovative architectural experiment in China.